ADVOKASI KEBIJAKAN PENINGKATAN PARTISIPASI PRIA DALAM PROGRAM KELUARGA BERENCANA DI KECAMATAN BATUWARNO KABUPATEN WONOGIRI - Oktaviana, Ita; Astuti, Retno Sunu; Santoso, R Slamet (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro)
Population growth in Indonesia is increasing and uncontrolled, need to overcome it through family planning programs. However, in the implementation of the family planning program in Batuwarno District, Wonogiri Regency, male participation is still low. Whereas the Male Operation Method which is part of the Long Acting Reversible Contraceptive Method can reduce the rate of population growth. This study used qualitative research methods. The purpose is to analyze the policy advocacy of increasing male participation and its inhibiting factors. The theory used is theory advocacy by Ramaditya Rahardian. The results of the research are policy advocacy that implement through the Priyo Utomo group in Batuwarno sub-district has not succeeded in increasing male participation. The results of policy advocacy not as expected. The strategy of Communication, Information and Education, and socialization of Male Operation Method and use print media. The inhibiting factors are the religious, less of human resources, less of human resource, less of budget, less of coordination, and technical negligence. The researcher recommend is formulating a regulation for male participation so that can encourage increased male participation